Soil Chemical Characteristics of Organic and Conventional Agriculture - Aziz, Muhammad Abdul; Hazra, Fahrizal; Salma, Selly; Nursyamsi, Dedi Nursyamsi (JOURNAL OF TROPICAL SOILS, 2016)
Use of chemical fertilizers and pesticides on intensive land of both lowland and upland food crops have been shown to increase agricultural productivity significantly. Research aimed to study soil chemical characteristics and soil pesticide residues at some crops of organic and conventional farms. The research was carried out inÂ  Laboratory of Soil Chemistry, Indonesian Soil Research Institute and in Laboratory of Agrochemical Residue, Indonesian Agricultural Environment Research Institute, Bogor from February to July 2015. Soil samples at 0-10 cm depth were taken compositely from broccoli (Brassica oleracea), carrots (Daucus carota), maize (Zea mays), and tomatoes (Solanum lycopersicum) farms in Bogor Regency as well as from rice field in Tasikmalaya Regency at both organic and conventional farms. Soil chemical characteristics were analyzed include: soil organic-C (Walkey and Black), total-N (Kjeldahl), potential-P (HCl 25%), available-P (Olsen), potential-K (HCl 25%), available-K (NH4OAc 1 N pH 7), CEC (NH4OAc 1 N pH 7), and pH (soil : water = 1: 5), while pesticide residues included levels of organochlorine (lindane, aldrin, heptaklor, dieldrin, DDT, endosulfan); organophosphates (diazinon, fenitrotin, metidation, paration, profenofos); and carbamates (carbofuran, MIPC, BPMC) in the soil by using Gas Chromatography method. Results showed that levels of soil organic-C, total-N, potential and available-P, potential and available-K, CEC, pHÂ  at organic farms were higher than those at conventional farms. Some pesticide residues compound (organochlorines, organophosphates, and carbamates) were detected at conventional farm, while those at organic farm were not detected (trace).Keywords: Conventional farm, organic farm, pesticide residues, soil properties. [How to Cite: Muhammad AA, F Hazra, S Salma and D Nursyamsi. 2016. Soil Chemical Characteristics of Organic and Conventional Agriculture. J Trop Soils 21: 19-25. Doi: 10.5400/jts.2016.21.1.19]Â